(untitled) (The NOUN Journal of Agricultural Research and Development (NJARD), 2025)
Efforts towards achieving food security will be fruitless without understanding the dynamics of soils and as well as classifying them, since soil is the major medium for plant growth. Thus, this research aimed at characterizing and classifying the soils along the toposequence of Amainyi-nta in Ihitte/Uboma Local Government Area of Imo State. The pedons were sited along the toposequece with one soil profile pit representing each topographic position. The soil profile pits were examined and sampled for laboratory analyses of the physical and chemical properties. The morphological examination of the soil profiles revealed various shades of brownish soil colour. The bulk density values did not exceed 1.63 g/cm3. The soils’ total porosity values ranged from 39.10 to 70.09. Argillic horizons were expressed by sandy clay loam and sandy clay dominance in the subsurface horizons. The soils were low in organic carbon and total nitrogen. The soil pH values ranged from 4.73 to 6.50 while the maximum cation exchange capacity value obtained was 7.21 in the surface soil of AMA 1. AMA 1 and AMA 2 were classified as Typic Paleudults while AMA 3 was classified as Aquic Arenic Paleudults. One of the best management options of these soils is to plant acid-tolerant crops to minimize cost of production through liming.